Book Insecurity: More Than Lack of Access - Whittingham, Jeff; Wake, Donna; Shaw, Erin; Miller, Rachelle (Language and Literacy / Langue et littératie, 2025)
This study explores the phenomenon of book insecurity, a condition extending beyond lack of access to books, to the emotional and mental state of students' attitudes toward obtaining and owning books. Grounded in Maslow's hierarchy of needs, the study posits that book scarcity intersects with multiple levels of human needs. The study introduces and defines the concept of "book insecurity" as a state where individuals lack access to books and experience anxiety related to book acquisition, retention, or loss. The findings underscore the need for multifaceted interventions to improve book access and foster a culture of reading among low-income students.